¿Un nuevo enfoque en la gestión migratoria? Tensiones y contradicciones de la política migratoria en el sexenio de López Obrador (2018-2024) - Délano Alonso, Alexandra; Gil Everaert, Isabel (El Colegio de México A.C., 2025)
Mexico has established itself as a country of mixed mobility flows: emigration, immigration, return, transit, asylum, and temporary settlement. This article analyzes the migration policy as the State’s primary instrument in this reality, focusing on Andrés Manuel López Obrador’s (AMLO) six-year term (2018–2024) and the idea of a “new era in migration policy.” We identify three contradictions and three specific omissions. 1) Tension between long-term, structurally focused proposals aimed at community development, poverty reduction, and inequality as strategies to address the root causes of migration, and the migration containment actions and border militarization in collaboration with the United States. 2) Limited response, attention, and resources dedicated to the support of Mexicans abroad, a priority in the public discourse. 3)Tensions in the role of organized civil society, which shifts from being considered an ally to being confronted and excluded from decision-making spaces and discussions on migration issues. The three significant omissions are: asylum policy, internal displacement, and integration policies for migrants, refugees, and returnees.